Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,x^2-5x+4=x^2-4x-x+4=x\left(x-4\right)-\left(x-4\right)=\left(x-4\right)\left(x-1\right)\)
\(b,4x^2-4x-3=4x^2-2.2x.1+1-3-1=\left(2x-1\right)^2-4=\left(2x-1-2\right)\left(2x-1+2\right)=\left(2x-3\right)\left(2x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x8 + x4 + 1
= x8 + 2x4 + 1 - x4
= [(x4)2 + 2x4 + 1] - x4
= (x4 + 1)2 - (x2)2
= ( x4 - x2 + 1 ) ( x4 + x2 + 1 )
x8+x+1
=(x8−x2)+(x2+x+1)
=x2(x6−1)+(x2+x+1)
=x2(x2+1)(x3−1)+(x2+x+1)
=x2(x3+1)(x−1)(x2+x+1)+(x2+x+1)
=(x2+x+1)[x2(x3+1)(x−1)+1]
=(x2+x+1)[x2(x4−x3+x−1)+1]
=(x2+x+1)(x6−x5+x3−x2+1)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4+1\)
\(=x^4+2x^2+1-2x^2\)
\(=\left(x^2+1\right)^2-2x^2\)
\(=\left(x^2-\sqrt{2}x+1\right)\left(x^2+\sqrt{2}x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=yz(x^2+5x-14)
=yz(x^2-2x+7x-14)
=yz[x(x-2)+7(x-2)
=yz(x-2)(x+7)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(x^2-5x+4\)
\(=x^2-x-4x+4\)
\(=x\left(x-1\right)-4\left(x-1\right)\)
=\(\left(x-1\right)\left(x-4\right)\)
b)\(4x^2-4x-3\)
\(=4x^2+2x-6x-3\)
\(=2x\left(2x+1\right)-3\left(2x+1\right)\)
\(=\left(2x-3\right)\left(2x+1\right)\)
a) \(x^2-5x+4\)
\(=x^2-4x-x+4\)
\(=\left(x^2-4x+4\right)-x\)
\(=\left(x-2\right)^2-x\)
\(=\left(x-2\right)^2-\left(\sqrt{x}\right)^2\)
\(=\left(x-2-\sqrt{x}\right)\left(x-2+\sqrt{x}\right)\)
b) \(4x^2-4x-3\)
\(=4x^2-4x+1-4\)
\(=\left(2x+1\right)^2-2^2\)
\(=\left(2x+1-2\right)\left(2x+1+2\right)\)
\(=\left(2x-1\right)\left(2x+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(4a^2b^2-\left(a^2+b^2-c^2\right)^2\)
\(=4a^2b^2-2ab\left(a^2+b^2-c^2\right)+2ab\left(a^2+b^2-c^2\right)-\left(a^2+b^2-c^2\right)^2\)
\(=2ab\left[2ab-\left(a^2+b^2-c^2\right)\right]+\left(a^2+b^2-c^2\right)\left[2ab-\left(a^2+b^2-c^2\right)\right]\)
\(=\left(2ab+a^2+b^2-c^2\right)\left(2ab-a^2-b^2+c^2\right)\)
\(=\left(a^2+ab+ab+b^2-c^2\right)\left[c^2-\left(a^2-ab-ab+b^2\right)\right]\)
\(=\left[a\left(a+b\right)+b\left(a+b\right)-c^2\right]\left[c^2-\left(a\left(a-b\right)-b\left(a-b\right)\right)\right]\)
\(=\left[\left(a+b\right)^2-c^2\right]\left[c^2-\left(a-b\right)^2\right]\)
\(=\left[\left(a+b\right)^2-c\left(a+b\right)+c\left(a+b\right)-c^2\right]\left[c^2+c\left(a-b\right)-c\left(a-b\right)-\left(a-b\right)^2\right]\)
\(=\left[\left(a+b\right)\left(a+b-c\right)+c\left(a+b-c\right)\right]\left[c\left(c+a-b\right)-\left(a-b\right)\left(c+a-b\right)\right]\)
\(=\left(a+b+c\right)\left(a+b-c\right)\left(c+a-b\right)\left(c-a+b\right)\)